2020
DOI: 10.1371/journal.pone.0237710
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and self-care behaviours among patients with type 2 diabetes mellitus in Ghana

Abstract: Background Diabetes often coexists with other medical conditions and is a contributing cause of death in 88% of people who have it. The study aimed at evaluating medication adherence, self-care behaviours and diabetes knowledge among patients with type 2 diabetes mellitus in Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 35 publications
11
42
5
3
Order By: Relevance
“…There was no statistical relation between the taking of medications and the variables tested in this research. As opposed to these findings, studies from Africa and Saudi Arabia (22)(23) found an association with the variables Age and Educational level, according to which younger people and those with low educational levels adhered the least to this activity. These results highlight the importance of a health education adapted to the needs of the patient, going beyond raising the awareness of the individual about the adherence to the medication treatment to control the diabetes.…”
Section: Variablesmentioning
confidence: 59%
“…There was no statistical relation between the taking of medications and the variables tested in this research. As opposed to these findings, studies from Africa and Saudi Arabia (22)(23) found an association with the variables Age and Educational level, according to which younger people and those with low educational levels adhered the least to this activity. These results highlight the importance of a health education adapted to the needs of the patient, going beyond raising the awareness of the individual about the adherence to the medication treatment to control the diabetes.…”
Section: Variablesmentioning
confidence: 59%
“…Multiple medications could contribute to non-adherence since such patients have divided commitment to managing several comorbidities. Also, since majority of our study population had low or no formal education (166,64.7%), this could explain the high levels of non-adherence to antidiabetic medications as further reported by previous studies in Ghana (20). The reason for this nding could be that as the antidiabetic regimen becomes complex, those with higher level of education are expected to easily understand such and thus effectively follow their treatment regimen.…”
Section: Prevalence Of Non-adherencementioning
confidence: 66%
“…Self-care practices in diabetes patients are crucial to keep the illness under control and prevent complications. Effective management of diabetes will be a difficult task without adequate understanding of the existing level of practice related to diabetes self-care [49,[52][53][54].…”
Section: Mean±sd Rii Rankingmentioning
confidence: 99%
“…Not smoking was associated with being female and being retired. [52] Participant's age, educational level, and practice of self-care behaviours influenced adherence to anti-diabetes medication. Participants aged 70 years and above were less likely to be non-adherent to medication as compared to those below 50 years.…”
Section: Mean±sd Rii Rankingmentioning
confidence: 99%